PENGARUH MOTIVASI, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DI PT. PELAYARAN AGUNG SAMUDRA DI BALIKPAPAN - Nofandy, Farhan; Hadiyatno, Didik; Arrywibowo, Imam (Jurnal GeoEkonomi, 2024)
The purpose of this study is to determine the Effect of Motivation, Work Discipline and Work Environment on Job Satisfaction at PT. Agung Samudra Cruise in Balikpapan. Data collection was carried out by distributing questionnaires with the number of respondents as many as 40 employees of PT. Great Ocean Voyage, this research method uses quantitative methods. The sampling technique in this study used purposive sampling techniques. Statistical tests and data processing were carried out using Partial Least Square (PLS) with SmartPLS program version 3.0. The results showed that the Work Environment variable had a positive and significant effect on job satisfaction while the motivation and Work Discipline variables had no effect on job satisfaction.